Aberrant migration and surgical removal of a heartworm (Dirofilaria immitis) from the femoral artery of a cat. (20th February 2018) - Oldach, Maureen S.; Gunther‐Harrington, Catherine T.; Balsa, Ingrid M.; McLarty, Ehren M.; Wakeman, Kyle A.; Phillips, Kathryn L.; Honkavaara, Juhana; Visser, Lance C.; Stern, Joshua A.
Abstract : A cat was evaluated for an acute‐onset of right pelvic limb paresis. Thoracic radiographs revealed normal cardiac size and tortuous pulmonary arteries. Abdominal ultrasound identified a heartworm (HW) extending from the caudal abdominal aorta into the right external iliac artery and right femoral artery. The cat was HW‐antigen positive. Echocardiography revealed a HW within the right branch of the main pulmonary artery and evidence of pulmonary hypertension. An agitated‐saline contrast echocardiogram revealed a small right to left intracardiac shunt at the level of the atria. Surgical removal of the HW was performed with no substantial postoperative complications. There was return of blood flow and improved motor function to the limb. The cat remains mildly paretic on the affected limb with no other clinical signs.